Distinct dynamic behavioural response to social exclusion in male patients with a history of alcohol dependence - Chen, Ke; Wüstenberg, Torsten; Stiglbauer, Victoria; El-Ahmad, Linda; Rosenthal, Annika; Pelz, Patricia; Gold, Stefan M.; Heinz, Andreas; Sebold, Miriam (Addiction biology, 2023)
Social exclusion contributes to alcohol consumption, whereas the development of alcohol dependence (AD) can in turn lead to the social exclusion of people with AD. Previous research observed altered neural responses to experimentally induced social exclusion (i.e., Cyberball game) in patients with AD. In addition, inflammation has been associated with both social behaviours and AD. Our study aimed to investigate the dynamic behavioural response and the inflammatory effects of social exclusion in male patients with a history of AD. ...
Online veröffentlicht am 31. Mai 2023
Gesehen am 19.12.2023